Antiplatelet Therapy in Noncardioembolic Stroke: A Review of Current Evidence - Krishnan, Kailash; Jusufovic, Mirza; Sandset, Per Morten; Sandset, Else Charlotte (Seminars in Neurology, 2017)
Acute stroke is a leading cause of death and disability in the developed world. Among survivors, the risk of stroke recurrence is highest within the first few days, and up to 15% will be affected within the first year. In the case of noncardioembolism, antiplatelets, such as aspirin, clopidogrel, and the combination of aspirin and dipyridamole, remain the mainstay of treatment. Aspirin given immediately is beneficial, but when combined with clopidogrel is associated with a higher risk of bleeding. Dual antiplatelet therapy of aspirin and dipyridamole was no more effective than clopidogrel in reducing stroke recurrence. In symptomatic extracranial atherosclerosis, surgery within 2 weeks of the index event will benefit, but in strokes due to intracranial atherosclerosis and small vessel disease, medical therapy alone is recommended. The purpose of this review is to discuss the various trials of antiplatelet therapies in acute and long-term stroke prevention in mechanisms excluding cardioembolism.
Keywords: ischemic stroke; antiplatelets; stroke prevention; recurrent stroke